2012
DOI: 10.1063/1.4734686
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of CdSe/ZnS quantum dots using medium energy ion scattering

Abstract: Enhanced charge detection of spin qubit readout via an intermediate state Appl. Phys. Lett. 101, 233101 (2012) Tunable Dirac cone in the rectangular symmetrical semiconductor quantum dots array Appl. Phys. Lett. 101, 222108 (2012) Designer Ge quantum dots on Si: A heterostructure configuration with enhanced optoelectronic performance Appl. Phys. Lett. 101, 223107 (2012) From fabrication to mode mapping in silicon nitride microdisks with embedded colloidal quantum dots Appl. Phys. Lett. 101, 161101 (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…The inset depicts the decrease in F atoms per QD due to ion beam damage. The ion beam damage on the MEIS spectra was maximized at an areal ion dose of 2.5 × 10 16 ions/ cm 2 . The spectra were acquired using 100-keV He + at a scattering angle of 130°with a 10-μm ion beam without rastering.…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…The inset depicts the decrease in F atoms per QD due to ion beam damage. The ion beam damage on the MEIS spectra was maximized at an areal ion dose of 2.5 × 10 16 ions/ cm 2 . The spectra were acquired using 100-keV He + at a scattering angle of 130°with a 10-μm ion beam without rastering.…”
Section: Notesmentioning
confidence: 99%
“…13,14 Nanoparticle (NP) analysis via conventional MEIS has also been reported. 15,16 To minimize the ion beam damage in these cases, the samples were generally scanned over a large area, thus rendering it difficult to measure the composition profiles of the NPs, particularly those highly susceptible to ion beam damage.…”
mentioning
confidence: 99%
“…Details of the data analysis are described in Refs. [20,21,22,29,28]. The ion scattering intensities were analyzed by using the PowerMEIS program [29].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, its use to analyze nanostructured systems has drawn great attention due to its potential as a tool for the characterization of the shape, size, local composition and stoichiometry of NPs systems [23][24][25][26]. Particularly on core@shell NPs, it has been recently demonstrated that MEIS is a powerful technique to investigate their compositional and morphological properties, such as the size of the core, thickness of the shell, as well as their local compositions with sub-nanometer resolution [27,22,26,28]. In addition, the recent development of the PowerMEIS software has expanded the possibilities of using MEIS, allowing to simulate and model MEIS spectra of any kind of nanostructured system, of any kind of shape, composition and spatial distribution [20,21,22,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Due to these properties, several recent studies explored and used the potential of elastic scattering -mainly the Medium-Energy Ion Scattering (MEIS) methodology -for analysis of colloidal nanocrystals [5], [6], [7]. As many of these studies demonstrate, enhanced scattering cross sections, and thus also lower sample material amounts necessary for the analysis can be achieved e.g.…”
Section: Introductionmentioning
confidence: 99%